Educação de Jovens e Adultos: formação continuada colaborativa entre professores da sala comum e da educação especial - Bueno, Melina Brandt (2018)
Considering the public and specificities that constitute Youth and Adult Education, it is necessary to reflect on their pedagogical spaces and times and their distinctions in relation to those of regular education, as well as the pedagogical practices developed with the target public of the education especially in this modality. Thus, it is established as a general objective of the present study: to analyze together with the teachers of Youth and Adult Education and the Special Education their practices. And as specific objectives: (a) characterize the conceptions and pedagogical practices of these teachers with the target public student of special education (b) develop a program of collaborative training among these teachers, aiming at the reflective process of teaching practice and possibilities of acting in an inclusive context. Under a qualitative approach, the study is characterized as a collaborative research, involving eight participants, one of whom is a special education teacher and seven are teachers of curricular subjects, active in Youth and Adult Education. The research was carried out in a municipal public school, in a city in the interior of the state of São Paulo. The data collection and analysis procedures were organized in two stages: Characterization of the pedagogical practice and Collaborative Training. The instruments used are: observation scripts; characterization questionnaires; semi-structured interview scripts; field journal; initial roadmap for collaborative training; guiding questions for collaborative training; virtual classroom. The collected data were analyzed and organized using the categorical content analysis technique. The results of the research present aspects related to: initial conceptions of the teachers about the school inclusion and implications in the teaching performance; training demands; teaching planning and teaching performance; limits and possibilities of articulation between teachers; contributions of Collaborative Training. The main considerations are the relevance of the proposal of continuing training in service to the Youth and Adult Education teachers that work with the target audience of special education, which includes theoretical aspects, situations experienced by teachers and reflection on the teaching practice, as well as the importance of collaborative work among teachers, which needs to be made possible and facilitated.